The Impact of Digital Transformation on The Application of Risk-Based Auditing in Jordanian Public Shareholding Industrial Companies - Rabi, Ala' Mohammad (Journal of Posthumanism, 2024)
This study aimed to explore the impact of digital transformation on the application of risk-based auditing in Jordanian public shareholding industrial companies. To achieve the study's objectives, a descriptive-analytical approach was adopted. The study population consisted of all Jordanian public shareholding industrial companies that are still operating, totaling 46 companies distributed across nine different industrial sectors, according to the Companies Guide bulletin published on the Amman Stock Exchange website for the year 2024. The study sample included the main management departments of these companies. A comprehensive survey method was used to select the sample, resulting in the inclusion of all 46 Jordanian public shareholding industrial companies. The study's sampling unit targeted employees from the following departments within these companies: Finance, Internal Audit, and Information Technology. The targeted positions included Department Manager, Section Head, Accountant, Internal Auditor, and IT employee. To analyze the study data and test the hypotheses, the Statistical Package for Social Sciences (SPSS V.20) was used. After conducting the statistical analysis, the study revealed several key findings, the most notable of which was that digital transformation positively impacts the application of risk-based auditing in Jordanian industrial companies. This is due to the advanced tools and modern technologies provided by digital transformation, which enhance the efficiency and accuracy of risk-based auditing procedures. The study also presented several recommendations, the most important of which is the need for Jordanian industrial companies to establish an integrated system that combines digital technology, digital innovation, and digital governance processes to comprehensively implement risk-based auditing procedures.